Hydroxychloroquine Inhibits Macrophage Activation and Attenuates Renal Fibrosis After Ischemia-Reperfusion Injury - Zheng, Haofeng; Zhang, Yannan; He, Jiannan; Yang, Zhe; Zhang, Rui; Li, Lei; Luo, Zihuan; Ye, Yongrong; Sun, Qiquan (Frontiers in Immunology, 2021)
Chronic kidney disease (CKD), which is associated with high morbidity, remains a worldwide health concern, while effective therapies remain limited. Hydroxychloroquine (HCQ), which mainly targets toll-like receptor-7 (TLR-7) and TLR-9, is associated with a lower risk of incident CKD. Taking into account that TLR-9 is involved in the development of renal fibrosis and serves as a potential therapy target for CKD, we investigated whether HCQ could attenuate CKD via TLR-9 signal pathway. The effects of HCQ on renal tubulointerstitial fibrosis were further explored using a mouse model of renal tubulointerstitial fibrosis after ischemia/reperfusion injury. Bone marrow-derived macrophages were isolated to explore the effects of HCQ in vitro. Judicious use of HCQ efficiently inhibited the activation of macrophages and MAPK signaling pathways, thereby attenuating renal fibrosis in vivo. In an in vitro model, results showed that HCQ promoted apoptosis of macrophages and inhibited activation of macrophages, especially M2 macrophages, in a dose-dependent manner. Because TLR-7 is not involved in the development of CKD post-injury, a TLR-9 knockout mouse was used to explore the mechanisms of HCQ. The effects of HCQ on renal fibrosis and macrophages decreased after depletion of TLR-9 in vivo and in vitro. Taken together, this study indicated that proper use of HCQ could be a new strategy for anti-fibrotic therapy and that TLR-9 could be a potential therapeutic target for CKD following acute kidney injury.